2020
DOI: 10.1021/acs.biomac.0c00108
|View full text |Cite
|
Sign up to set email alerts
|

Toward Bio-Based Epoxy Thermoset Polymers from Depolymerized Native Lignins Produced at the Pilot Scale

Abstract: Producing the next generation of thermoset polymers from renewable sources is an important sustainability goal. Hydrogenolysis of pinewood lignin was scaled up for the first time from lab scale to a 50 L pilot-scale reactor, producing a range of depolymerized lignin oils under different conditions. These lignin hydrogenolysis oils were glycidylated, blended with bisphenol A diglycidyl ether, and cured to give epoxy thermoset polymers. The thermal and mechanical properties of the epoxy polymers were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 50 publications
2
71
0
Order By: Relevance
“…The future of aromatic thermosets relies on the operation of commercial-scale biorefineries for a stable and cost-effective supply of lignin-derived phenols or cellulosic-based furanics for materials production, especially for precursors like vanillin or eugenol that currently are too expensive to divert to polymer products. The existing chemical processes used to produce biobased aromatics from LCB face many challenges, such as low product yields, complex/expensive separations, and high levels of waste generation . There are several approaches to overcome these challenges.…”
Section: Future Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The future of aromatic thermosets relies on the operation of commercial-scale biorefineries for a stable and cost-effective supply of lignin-derived phenols or cellulosic-based furanics for materials production, especially for precursors like vanillin or eugenol that currently are too expensive to divert to polymer products. The existing chemical processes used to produce biobased aromatics from LCB face many challenges, such as low product yields, complex/expensive separations, and high levels of waste generation . There are several approaches to overcome these challenges.…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…Depolymerization of the LCB components to their respective monomers (i.e., phenolic compounds [lignin] and sugars [cellulosics]) can overcome the aforementioned challenges through increased functionality, consistency, and value. , Lignin can be depolymerized by catalytic, , enzymatic, or pyrolytic pathways to yield mixtures of biophenols that correspond to the H, G, and S phenylpropanoid units. Several functional groups may be present in these biophenols depending on the depolymerization strategy, including aliphatic/aromatic hydroxy, methoxy, aldehyde, carboxylic acid, alkyl, allyl, and alkenyl groups, and many of these chemical handles can be leveraged to generate safer, renewable thermosets. ,,,,, Cellulosics similarly can be depolymerized to sugars and further converted into platform furanics, such as hydroxymethylfurfural (HMF), through continued acid-catalyzed dehydration. ,, Together, lignin-derived phenolics and cellulosic-derived furanics can significantly improve the properties of renewable thermosets, and moreover, their inherent functionalities can be leveraged to generate performance-advantaged materials (i.e., polymers with improved properties relative to those of the incumbent) that can be recycled or further modified for unique applications.…”
Section: Introductionmentioning
confidence: 99%
“…16 Torr et al showed that a hydrogenolysis lignin oil or a part of the hydrogenolysis oligomers can be used as a partial replacement for BPA in the synthesis of epoxy resins. [17][18][19] However, a full BPA replacement was unsuccessful in their study. Successful replacement of p-nonylphenol by RCF lignin oligomers in the synthesis of resin and varnish used in printing inks was demonstrated.…”
mentioning
confidence: 94%
“…On the other hand, the setbacks for the direct use of industrial lignin instead of BPA toward epoxidation can be found in its low reactivity and low solubility in organic solvents, both somewhat dependent on the source of lignocellulosic components and the processing method. The depolymerization of lignin, using procedures such as pyrolysis, causes the disintegration of lignin macromolecules into phenolic compounds with a lower molecular weight, such as guaiacol, methyl guaiacol, and vanillin [8,9]. These lignin-derived molecules are more soluble and more reactive than lignin itself; thus, their phenolic structure with specific functional groups makes them proper candidates for direct glycidylation or epoxidation by epichlorohydrin (ECH).…”
Section: Introductionmentioning
confidence: 99%